2016
DOI: 10.1159/000453554
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Health Care Appointment Non-Adherence on Graft Outcomes in Kidney Transplantation

Abstract: Background: Non-adherence to medication is a well-studied and known cause of late allograft loss, but it is difficult to measure and prospectively monitor. The aim of this study was to assess if appointment non-adherence was correlated with medication non-adherence and a predictor of graft outcomes. Methods: This was a longitudinal cohort study that used the National United States Renal Data System and veterans affairs health records data with time-to-event analyses conducted to assess the impact on graft and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 29 publications
4
48
0
1
Order By: Relevance
“…Dew et al concluded from a meta‐analysis of 147 transplantation studies that nonadherence in renal allograft recipients was highest among solid organ transplant recipients, reaching 36 cases per 100 patients per year . Nonadherence has been associated with graft loss, and results from a recent meta‐analysis indicated that the odds of allograft failure increased sevenfold in nonadherent renal transplant recipients . Furthermore, nonadherence has been recognized as an independent risk factor for the development of de novo donor‐specific antibodies, a major cause of graft loss …”
Section: Introductionmentioning
confidence: 99%
“…Dew et al concluded from a meta‐analysis of 147 transplantation studies that nonadherence in renal allograft recipients was highest among solid organ transplant recipients, reaching 36 cases per 100 patients per year . Nonadherence has been associated with graft loss, and results from a recent meta‐analysis indicated that the odds of allograft failure increased sevenfold in nonadherent renal transplant recipients . Furthermore, nonadherence has been recognized as an independent risk factor for the development of de novo donor‐specific antibodies, a major cause of graft loss …”
Section: Introductionmentioning
confidence: 99%
“…The importance of these particular domains, or others, have not yet been sufficiently tested or demonstrated for ESRD patients who have received a kidney transplant. The data presented by Taber et al [1 ] clearly suggest that our model of requisite behaviors for kidney transplant patients needs to extend beyond medication taking, and include, at least, appointment adherence as well.…”
mentioning
confidence: 97%
“…In their article in this issue, Taber et al [1] , examine the role of appointment non-adherence in graft outcomes in kidney transplantation. They find that appointment non-adherence is a significant and independent predictor of negative outcome beyond medication non-adherence.…”
mentioning
confidence: 99%
“…Further, costs of the intervention will be compared with gains in utility based on the SF12. Adherence to appointments, staff time in administering the intervention and days in hospital during the study period will be collected retrospectively at the study end and reported to the SSRL by the study site leads 50. The site leads will remain blind to participant allocation and the SSRL will incorporate the information into the final dataset and deidentify it before providing it to the research team for analysis.…”
Section: Outcome Measuresmentioning
confidence: 99%